The Effet of pH and Pasteurisation Temperature on Water Content and Vitamin C Content From Tomato Sauce (Lycopersicum esculentum Mill) - Nurhidayati Nurhidayati; Ruka Yulia; Putri Meutia Sari (Universitas Serambi Mekkah, 2019)
The purpose of this study was to determine the effect of pH control and pasteurization temperature on making tomato sauce on the quality produced. This study uses a factorial completely randomized design (RAL) 2 which is used is the measurement of pH (R) (3, 4 and 5 and pasteurization temperature (T) (70˚C, 80˚C and 90˚C). , vitamin C and organoleptic tests (color and taste) .The results of the research showed the best treatment on the combination of R2T2 treatment with a pH regulator 4 and 800C pasteurization temperature which produced a good quality tomato sauce with chemical properties namely 77.24% moisture content, vitamin C 0.059%, organoleptic taste 3.74 (likes) and color 3.87 (likes).